Penilaian resiko keamanan siber kampus menggunakan NIST cybersecurity framework 1.1 dengan Peringkat PEGI - handoyo, eko; Aprillya, Mala Rosa (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2024)
The development of information technology is currently progressing rapidly. The threat of information technology that occurs makes many agencies and companies suffered losses. Information security aims to make the information that is guaranteed confidentiality, integrity and its availability. The many threats of information security that have a major impact on institutions need to be carried out by cyber security risk assessment. The campus is one of the implementation of cyber implementation in the scope of education with the amount of data and information that needs to be saved. This study uses the standard Nist Cybersecurity Framework 1.1. is a framework for directing organizations to cyber security activities and security risk assessments. Whereas PEGI is an assessment method used as a solution to analyze e-government where the assessment is 4 lavel, which is very good, good, less and very less. The results of this study obtained the value of the security of the Cyber campus security place the institution at a value of 2.08 with the conclusions that the campus cyber security system is still in less level so it needs to be improved to provide good Cyber Cyber security and data security and information security.